2008
DOI: 10.1038/nmeth.1259
|View full text |Cite
|
Sign up to set email alerts
|

A nano-positioning system for macromolecular structural analysis

Abstract: Very often, the positions of flexible domains within macromolecules as well as within macromolecular complexes cannot be determined by standard structural biology methods. To overcome this problem, we developed a method that uses probabilistic data analysis to combine single-molecule measurements with X-ray crystallography data. The method determines not only the most likely position of a fluorescent dye molecule attached to the domain but also the complete three-dimensional probability distribution depicting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
238
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(250 citation statements)
references
References 33 publications
(66 reference statements)
5
238
0
Order By: Relevance
“…Therefore, the variance of the FRET efficiency distribution in the TD-A1 experiment is much smaller for the tetramer than for the dimer. Several groups have recently developed tools to calculate an accurate distribution of the distance between the donor and acceptor by appropriate modeling of fluorophores and linkers for macromolecules with well-defined structures (64)(65)(66)(67)(68)(69). This calculation may allow for a more quantitative comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the variance of the FRET efficiency distribution in the TD-A1 experiment is much smaller for the tetramer than for the dimer. Several groups have recently developed tools to calculate an accurate distribution of the distance between the donor and acceptor by appropriate modeling of fluorophores and linkers for macromolecules with well-defined structures (64)(65)(66)(67)(68)(69). This calculation may allow for a more quantitative comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been developed to account for this uncertainty. These methods include Bayesian statistical methods and molecular dynamics modeling to calculate a region that the fluorophore attached to the protein will likely occupy during the excited-state lifetime (30,31). Although these computational methods improve the ability to estimate the location of the fluorophore in space, an experimental method that precludes the use of computation to find backbone positions would be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…The data are analyzed using Bayesian parameter estimation to generate a probability density function for the unknown position (i.e., the position of the antennae dye molecule). 16 Yeast RNAP II open complexes containing TBP, TFIIB, TFIIF, RNAP II, and heteroduplex DNA (i.e., contains an engineered bubble around the transcription start site) were studied using a NPS. 15 Downstream DNA in open complexes was found to fluctuate between two locations: within and above the RNAP II cleft.…”
Section: Smfret Elucidates Structural Changes In Open Complexes and Ementioning
confidence: 99%
“…18 This discrepancy could potentially arise from differing experimental conditions, such as ion concentrations. 19 Interestingly, a NPS study found that in the absence of TFIIB, exiting RNA was more likely to contact the dock domain of RNAP II, but upon addition of TFIIB, the contact shifted toward the Rpb4-Rpb7 subunits, 16 suggesting that this switch could be regulated during early transcription.…”
Section: Smfret Elucidates Structural Changes In Open Complexes and Ementioning
confidence: 99%